Identità individuale come immagine - Spreafico, Andrea (SocietàMutamentoPolitica, 2013)
This essay sets out an approach to the study of those visual and verbal traces that, according to “common sense”, relate to individual identity. It will thus consider that identity as an image, locally constituted in the course of social interactions and open to description by the sociologist who – for example via videorecording – is able to capture not only its linguistic aspects but also, equally important, those related to its visible appearance.